Exploring hotel brand attachment: The mediating role of sentimental value. (July 2020) - Liu, Yan; Kou, Yan; Guan, Zhenzhong; Hu, JiaJing; Pu, Bo
Abstract: Brand attachment is at the core of building strong consumer brand relationships, which has important strategic significance for hotel enterprises and brands in acquiring a sustainable competitive advantage. Currently, neither the mechanisms underlying brand attachment nor the factors influencing hotel brand attachment are clearly understood. Functional, symbolic, and hedonic needs influence brand selection. This paper analyzed the effect of these three factors on consumers' perceived value and brand attachment. The mediating effects of customer sentimental value were also evaluated. This study expands our understanding of what determines brand attachment by showing that sentimental value mediates the relationships between functional value, symbolic value, hedonic value, and brand attachment. It also has managerial implications for the hotel industry.